Why conservation is failing and how it can regain ground - Freyfogle, Eric T. (Yale University Press, 2006)
Critics of environmental laws complain that such rules often burden people unequally, restrict individual liberty, and undercut private property rights. In formulating responses to these criticisms, the conservation effort has stumbled badly, says Eric Freyfogle in this thought-provoking book. Conservationists and environmentalists haven't done their intellectual homework, he contends, and they have failed to offer an understandable, compelling vision of healthy lands and healthy human communities. Freyfogle explores why the conservation movement has responded ineffectually to the many cultural and economic criticisms leveled against it. He addresses the meaning of good land use, describes the many shortcomings of 'sustainability', and outlines six key tasks that the cause must address. Among these is the crafting of an overall goal and a vision of responsible private ownership. The book concludes with a stirring message that situates conservation within America's story of itself and with an extensive annotated bibliography of conservation's most valuable voices and texts - important information for readers prepared to take conservation more seriously.